F. A. Hayek's genealogy - Bruce Caldwell; Hansjörg Klausinger (Duke University, Center for the History of Political Economy (CHOPE), 2021)
This working paper - like its companion, Caldwell and Klausinger 2021 - grew out of the authors' joint work on Hayek: A Life, 1899-1950 (Caldwell and Klausinger 2022) and it contains material supplementing it. This paper draws to a large extent on Friedrich Hayek's own investigations into the genealogical roots of his family. On the paternal side the family ancestry is traced back to the ennoblement of Friedrich's great-great-grandfather Josef Hayek in 1789. On the maternal side we enquire into the family trees of Fritz's grandfather Franz von Juraschek and his first and second wife, Johanna Stallner and Ida Pokorny. Finally, we look at the relationship between Fritz and two of his "distant cousins," the philosopher Ludwig Wittgenstein and Fritz's girlfriend in his youth and future second wife, Helene ("Lenerl") Bitterlich.
Keywords: 330; Friedrich Hayek; Juraschek; Wittgenstein; Vienna; genealogy